Relation between Rind Pigmentation and Internal Quality of Blood Orange ‘Sanguinelli’: Physicochemical and Sensory Studies - Tarancón, Paula; Cebrián, Begoña; Fernández-Serrano, Paula; Besada, Cristina (MDPI, 2022)
This study evaluated the relation between rind colour and the internal physicochemical and sensory qualities of ‘Sanguinelli’ blood oranges, one of the main blood orange cultivars grown in the Mediterranean region. To this end, 400 fruits were harvested in three different orchards and classified according to rind pigmentation intensity (slight, medium, intense, very intense). All fruits were individually evaluated by determining rind and pulp colour, total soluble solids, acidity, maturity index, juice yield, firmness, and size. Moreover, 71 consumers performed a triangle test to evaluate if fruit sensory properties depended on rind pigmentation. Our results revealed (for the first time) that pulp pigmentation and total soluble solid (TSS) content strongly depend on rind colouration. Among the fruit from the same orchard, the redder the pigmented fruit was (externally) the deeper the red pulp, and the higher the TSS became. This pattern was corroborated in the three orchards under study. Other characteristics, such as acidity, juice yield, firmness, and fruit size, did not depend on external pigmentation. Sensory studies showed that the more coloured the fruit, the higher the accumulated sugar content; consumers perceive these fruits as being sweeter than slightly pigmented ones. This information can be very useful for the citrus industry as external colour may become a quality index for blood oranges, as well as for consumers to make purchase decisions.